1981
DOI: 10.3109/01485018108999329
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of Lipids Between Spermatozoa and Seminal Plasma in Normal and Pathological Human Semen

Abstract: Normal and pathological semen were studied with regard to cholesterol and phospholipid content of sperm cells and seminal plasma. Spermatozoa from pathologic semen have similar concentrations of phospholipid-phosphorous and significantly higher cholesterol concentration than spermatozoa from normal semen. However, only oligoasthenospermic spermatozoa showed a significantly higher cholesterol/phospholipid ratio. Azoospermic seminal plasma showed the lowest values of both cholesterol and phospholipids, but the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…The decreased phospholipid values in spermatozoa thus suggest that there is a change in the phospholipid component of the sperm membrane which plays a major role in the fertilizing ability of spermatozoa. An aberrant phospholipid level in spermatozoa has also been reported previously in oligoasthenospermic and asthenozoospermic infertile patients (Huacuja et al, 1981). Phospholipids along with cholesterol play a significant role in maintaining the cohesiveness of sperm membrane structure and their ability to withstand physical and physiological stress (see Philips, 1972).…”
Section: Discussionmentioning
confidence: 69%
“…The decreased phospholipid values in spermatozoa thus suggest that there is a change in the phospholipid component of the sperm membrane which plays a major role in the fertilizing ability of spermatozoa. An aberrant phospholipid level in spermatozoa has also been reported previously in oligoasthenospermic and asthenozoospermic infertile patients (Huacuja et al, 1981). Phospholipids along with cholesterol play a significant role in maintaining the cohesiveness of sperm membrane structure and their ability to withstand physical and physiological stress (see Philips, 1972).…”
Section: Discussionmentioning
confidence: 69%
“…We used Chol as a molecule that provides rigidness to the membrane and polyunsaturated acids as agents promoting membrane fluidity. Sebastian et al (1987) and Huacuja et al (1981) suggested that there is a positive correlation between seminal PL and fertility and a negative correlation between seminal neutral lipids (i.e., Chol) and fertility. However little work is available on the pattern of different classes of lipids, their fractions in the seminal plasma (SP), and their influence on mammalian spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…The lipid profile in the sperm tail membrane is associated with physical properties that facilitate sperm motility and velocity (Connor et al 1998). Antioxidant (Lenzi et al 2000, Strzeżek et al 2004 and cholesterol contents in the seminal fluids (Huacuja et al 1981, Morales et al 2008, Saez et al 2011, as well as cholesterol acceptors that facilitate cholesterol efflux from the sperm during capacitation (Saez et al 2011), positively affect sperm quality.…”
Section: Introductionmentioning
confidence: 99%